2019
DOI: 10.3389/fncel.2019.00417
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Inhibitory Input to the Substantia Nigra in Experimental Parkinsonism

Abstract: The substantia nigra pars reticulata (SNr) is one of the output nuclei of the basal ganglia (BG) and plays a vital role in movement execution. Death of dopaminergic neurons in the neighboring nucleus, the substantia nigra pars compacta (SNc), leads to Parkinson's disease. The ensuing dopamine depletion affects all BG nuclei. However, the long-term effects of dopamine depletion on BG output are less characterized. In this in vitro study, we applied electrophysiological and immunohistochemical techniques to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…For example, although SN does not have GABAergic neurons, the SN pars reticulata (SNr) region has receptors for GABAergic projection exons ( 64 ). It is known that DA depletion induced by dopaminergic neuronal death in SN pars compacta (SNc) of PD patients affects GABAergic transmission in basal ganglia and this, in turn, possibly affected the expression of GABAergic receptors in SNr ( 65 ). Therefore, dysregulation of GABA receptor proteins in the SN of PD could be considered a consequence of dopaminergic neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although SN does not have GABAergic neurons, the SN pars reticulata (SNr) region has receptors for GABAergic projection exons ( 64 ). It is known that DA depletion induced by dopaminergic neuronal death in SN pars compacta (SNc) of PD patients affects GABAergic transmission in basal ganglia and this, in turn, possibly affected the expression of GABAergic receptors in SNr ( 65 ). Therefore, dysregulation of GABA receptor proteins in the SN of PD could be considered a consequence of dopaminergic neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…α-Synuclein being a synaptic protein, aberrant synaptic plasticity in SNpr, may contribute to pathophysiology of PD (Prescott et al, 2009). Faynveitz et al, (2019) demonstrated that 6-OHDA-induced depletion of dopamine in the SNpc neurons, results in reduced firing rate and periodicity of the SNr neurons, suggesting expansion of GABAergic inhibition within the SNr, and thus contributing to PD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…PD is well known to be caused by the progressive death of DA neurons in the substantia nigra of the midbrain, leading to a lack of DA in the striatum. Studies have shown that chronic DA depletion can enhance the transmission of GABA in the striatum, thus affecting cell and circuit activities, which are related to the pathogenesis of PD [ 40 ]. A study has shown [ 41 ] that patients with PD in Braak 3 exhibit an increased threshold of GABA medium spiny neurons, and patients with PD in Braak 4 exhibit decreased spontaneous GABA activity.…”
Section: Discussionmentioning
confidence: 99%